TBX21 correlates with an immunosuppressive tumor microenvironment and Treg/Th17 imbalance in prostate cancer - Wang, Heng; Liu, Zhaofei; Xu, Xiangjun; Wang, Qichao; Chang, Pingan; He, Lei; Ouyang, Jun (Frontiers in Oncology, 2026)
BackgroundProstate cancer (PCa) remains a major health burden, and identifying target molecules will provide new research ideas for treating PCa. TBX21 is a transcriptional factor with critical functions in tumor development, roles of which in PCa were studied herein.MethodsTBX21 expression was evaluated by RNA-seq, RT-PCR, Western blot, and immunohistochemistry in PCa tissues and cell lines. Functional assays were performed using LNCaP and 22RV1 cells with TBX21 knockdown to assess proliferation and apoptosis. Tumor growth and immune alterations were examined in xenograft and humanized immune cell models, while flow cytometry and Western blot were used to characterize immune cell subsets and effector molecules.ResultsTBX21 expression was significantly elevated in PCa tissues and cell lines. TBX21 knockdown was associated with reduced proliferation and increased apoptosis in vitro and suppressed tumor growth in vivo. In humanized xenografts, TBX21 silencing was accompanied by a decrease in regulatory T cells (Treg) and an increase in Th17 and cytotoxic CD8+ T cells, together with enhanced expression of effector molecules (TNF-α, GZMB). Co-culture experiments showed that TBX21-deficient tumor cells reduced the induction of CD25+Foxp3+ Treg cells from activated CD4+ T cells.ConclusionTBX21 is associated with tumor progression and an immunosuppressive microenvironment in PCa, underscoring its potential role in modulating the tumor–immune balance.